MIDDLESEX UNIVERSITY UK’S ERASMUS+ PROGRAMME PROVIDES FUNDING OPPORTUNITIES FOR USM STAFF AND STUDENTS MOBILITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
LONDON, February 2016 Universiti Sains Malaysia (USM) has been officially included as a partner country institution by Middlesex University under its International Credit Mobility programme, a new strand of the Erasmus+ programme which will enable both inward and outward mobility to and from countries outside the European Union.